Neural Signatures of Intransitive Preferences - Kalenscher, Tobias; Tobler, Philippe N.; Huijbers, Willem; Daselaar, Sander M.; Pennartz, Cyriel (Frontiers in Human Neuroscience, 2010)
It is often assumed that decisions are made by rank-ordering and thus comparing the (subjective value of) available choice options. Rank-ordering requires that alternatives are mentally represented at least on an ordinal scale. Because one alternative cannot be at the same time better or worse than another alternative, choices should satisfy transitivity (if alternative A is preferred over B, and B is preferred over C, A should be preferred over C). Yet, individuals often demonstrate striking violations of transitivity (preferring C over A). We used functional magnetic resonance imaging to study the neural correlates of intransitive choices between gambles varying in magnitude and probability of financial gains. Behavioral intransitivities were common. They occurred because participants did not evaluate the gambles independently, but in comparison with the alternative gamble presented. Neural value signals in prefrontal and parietal cortex were not ordinal-scaled and transitive, but reflected fluctuations in the gambles’ local, pairing-dependent preference-ranks. Detailed behavioural analysis of gamble preferences showed that, depending on the difference in the offered gambles’ attributes, participants gave variable priority to magnitude or probability and thus shifted between preferring richer or safer gambles. The variable, context-dependent priority given to magnitude and probability was tracked by insula (magnitude) and posterior cingulate (probability). Their activation-balance may reflect the individual decision rules leading to intransitivities. Thus, the phenomenon of intransitivity is reflected in the organisation of the neural systems involved in risky decision-making.